3D printing of cellulose/leaf-like zeolitic imidazolate frameworks (CelloZIF-L) for adsorption of carbon dioxide (CO2) and heavy metal ions. Issue 10 (13th February 2023) - Abdelhamid, Hani Nasser; Sultan, Sahar; Mathew, Aji P.
Abstract : Metal–organic frameworks (MOFs) have advanced several technologies. Abstract : Metal–organic frameworks (MOFs) have advanced several technologies. However, it is difficult to market MOFs without processing them into a commercialized structure, causing an unnecessary delay in the material's use. Herein, three-dimensional (3D) printing of cellulose/leaf-like zeolitic imidazolate frameworks (ZIF-L), denoted as CelloZIF-L, is reported via direct ink writing (DIW, robocasting). Formulating CelloZIF-L into 3D objects can dramatically affect the material's properties and, consequently, its adsorption efficiency. The 3D printing process of CelloZIF-L is simple and can be applied via direct printing into a solution of calcium chloride. The synthesis procedure enables the formation of CelloZIF-L with a ZIF content of 84%. 3D printing enables the integration of macroscopic assembly with microscopic properties, i.e., the formation of the hierarchical structure of CelloZIF-L with different shapes, such as cubes and filaments, with 84% loading of ZIF-L. The materials adsorb carbon dioxide (CO2 ) and heavy metals. 3D CelloZIF-L exhibited a CO2 adsorption capacity of 0.64–1.15 mmol g −1 at 1 bar (0 °C). The materials showed Cu 2+ adsorption capacities of 389.8 ± 14–554.8 ± 15 mg g −1 . They displayed selectivities of 86.8%, 6.7%, 2.4%, 0.93%, 0.61%, and 0.19% toward Fe 3+, Al 3+, Co 2+, Cu 2+, Na +, and Ca 2+, respectively. The simple 3D printing procedure and the high adsorption efficiencies reveal the promising potential of our materials for industrial applications.